1975
DOI: 10.1007/bf01482711
|View full text |Cite
|
Sign up to set email alerts
|

Exokrine Pankreasfunktion bei chronischer Niereninsuffizienz

Abstract: Pancreatic function tests were performed in 15 patients with advanced renal insufficiency. Pancreatic secretion was stimulated with CCK/PZ and secretin and 60 minutes later with bile given intraduodenally and CCK/PZ and secretin intravenously. The Wilcoxon-test showed that there were significantly higher lipase levels in serum and lower amylase amounts in duodenal juice compared to normal volunteers. No differences could be demonstratd for volume, maximal bicarbonate concentration, lipase and trypsin outputs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1976
1976
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…While impairment of the pancreatic exocrine function [3,4,15,17,22,36,41,42] and of amino acid absorption [27] in uremic conditions has been reported repeatedly in the literature, the only information available on the behavior of dipeptidase activities in the small intestinal mucosa in chronic renal in sufficiency has come from the investigations of Denneberg et al [14] in a group of 18 patients and a study from this laboratory [19] using rats with a mean body weight of 492 g. Evi dence obtained in animals [33,34] and man [12,25] that amino acids administered as di peptides are absorbed more rapidly than when given in the free form, suggests that an inti mate knowledge of the mucosal dipeptidase activities in chronic renal insufficiency may attain practical significance. Table I shows that, in confirmation of our previous findings in rats [19], a significant in crease of the activities of L-leucyl-L-proline and L-methionyl-L-proline dipeptidase was found to occur in uremia, while all other di peptidases investigated failed to reveal a significant rise or fall in activity.…”
Section: Discussionmentioning
confidence: 99%
“…While impairment of the pancreatic exocrine function [3,4,15,17,22,36,41,42] and of amino acid absorption [27] in uremic conditions has been reported repeatedly in the literature, the only information available on the behavior of dipeptidase activities in the small intestinal mucosa in chronic renal in sufficiency has come from the investigations of Denneberg et al [14] in a group of 18 patients and a study from this laboratory [19] using rats with a mean body weight of 492 g. Evi dence obtained in animals [33,34] and man [12,25] that amino acids administered as di peptides are absorbed more rapidly than when given in the free form, suggests that an inti mate knowledge of the mucosal dipeptidase activities in chronic renal insufficiency may attain practical significance. Table I shows that, in confirmation of our previous findings in rats [19], a significant in crease of the activities of L-leucyl-L-proline and L-methionyl-L-proline dipeptidase was found to occur in uremia, while all other di peptidases investigated failed to reveal a significant rise or fall in activity.…”
Section: Discussionmentioning
confidence: 99%
“…Amylase, lipase and trypsin outputs are the parame ters mostly used to study acinar cell function [10,11,[14][15][16][17][18], Variable results were found in the different studies (table II). The most consistent finding is a low amylase o u tp u t.…”
Section: Acinar Cell Functionmentioning
confidence: 99%
“…Indeed, plasma levels of total amylase are in creased in patients with renal failure [10,II,19,[24][25][26] with a higher proportion of total amylase constituted by the pancreatic isoenzyme [20,[24][25][26][27], Salivary amylase is also increased in uremic subjects but to a lesser degree [24][25][26], These changes obviously complicate the diagno sis of pancreatitis in the setting of renal insufficiency. Lipase Several reports have described elevated circulating levels of the enzyme in uremic subjects [15,[28][29][30][31][32], This elevation has been correlated with the degree of reduc tion in GFR in predialysis subjects [32,33], As expected from the size of the enzyme, hemodialysis has no effect on circulating levels [32], The mechanism of the increase is unclear since the enzyme is not known to be cleared by the kidney [29,34],…”
Section: Amylasementioning
confidence: 99%
See 2 more Smart Citations